(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this research, it has been highlighted on the different cultural patterns in the novel (the daughter of Tigris) by the well-known Iraqi novelist (Mohsen Al-Ramli), by applying the vocabulary and approach of cultural criticism, to clarify the apparent and implicit meanings in the novel, which the novelist expressed throught it about his cultural, political and social vision about Iraq during the occupation period, especially the issue of Iraqi women and their suffering